2002
DOI: 10.1038/sj.leu.2402361
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the null genotype of glutathione S-transferase-T1 in patients with acute myeloid leukemia: increased early death after chemotherapy

Abstract: We investigated the prognostic significance of genetic polymorphism in glutathione-S transferase mu 1 (GSTM1), glutathione-S transferase theta 1 (GSTT1), NAD(P)H:quinone oxidoreductase (NQO1) and myeloperoxidase (MPO), the products of which are associated with drug metabolism as well as with detoxication, in 193 patients with de novo acute myeloid leukemia (AML) other than M3. Of the patients, 64.2% were either homozygous or heterozygous for GSTT1 (GSTT1 + ), while 35.8% showed homozygous deletions of GSTT1 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 21 publications
2
15
1
3
Order By: Relevance
“…Our results are consistent with some recent studies but in acute myeloid leukaemia (AML) suggesting that the lack of the GSTT1 gene implies greater toxicity in these patients (25)(26)(27). Similar observations have been made in lung cancer (28).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with some recent studies but in acute myeloid leukaemia (AML) suggesting that the lack of the GSTT1 gene implies greater toxicity in these patients (25)(26)(27). Similar observations have been made in lung cancer (28).…”
Section: Discussionsupporting
confidence: 93%
“…A larger study conducted by the Children's Oncology Group in Ͼ600 children found no association between GSTM1 or GSTT1 polymorphisms and survival in childhood acute lymphoblastic leukemia (51). In children with acute myeloid leukemia, two different groups reported a significant relationship between increased risk for death due to toxicity and GSTT1 null genotype (52,53). In a study of Ͼ200 women with primary breast cancer, GSTT1 and GSTM1 null, and GSTP1 *B or *C variants were related to superior outcome (36,38).…”
Section: Discussionmentioning
confidence: 98%
“…The glutathione S-transferases (GSTs) have been implicated as susceptibility genes for a number of cancers. The homozygous deletions of GSTT1 [GSTT1(Ϫ)] group had a worse prognosis than either the homozygous or heterozygous for GSTT1 [GSTT1(ϩ)] group in acute myeloid leukemia (42). On the other hand, the GSTT1(Ϫ) genotype conferred the reduction in risk of relapse compared to the GSTT1(ϩ) in children with acute lymphoblastic leukemia (43,44).…”
Section: Discussion Differentially Expressed Genes In Each Type Of Nsmentioning
confidence: 99%